A Study on Fast Moving Consumer Goods Sector- A Comparitive Study on Dairy and Soft Drink Products - et al., Dr.T.Narayana Reddy (International Journal of Advanced Science and Technology, 2019)
A promotion announcing the benefits of a product or brand along with distribution efforts is observed in the rural markets in the FMCG category. The Customer satisfaction is essentially the culmination of a series of customer experiences or, the net result of the good ones minus the bad ones. It occurs, when the gap between customers’ expectations and their subsequent experiences has been closed. Today we notice there is shift being observed towards branded (FMCGs) Fast Moving Consumer Goods in rural areas as a result of Socio Economic & Political changes in the last 5 years. This has made rural areas more viable markets when compared to the urban areas. The Socio Economic and Political changes contributed to a great extent for changes in the life styles of countryside people who patronized branded Fast Moving Consumer Goods products. The Government policies/ approaches to advance education in restrict areas enhanced the brand awareness among the customers because of the presence at least one student pursuing higher education in a family. The diverse Government strategies are additionally being helpful for the province individuals (rural people) contributing for the in improvement in individuals income, image and mindfulness followed by a change in their lifestyles resulted in patronizing the branded products. Sales promotion is a tiny term incentive to be a magnet for the buy or sale of products and services. It includes all activities that are performed by the producers or by dealers or by businessmen to boost its sale over a period of time. Purpose behind sales promotion is to motivate and persuade the consumers to buy a certain product and to encourage repetitive purchase of that very product and enable repetitive purchase of that thing.